Successful Attenuation of Venous Thrombus Growth in Rabbits after the Administration of a Novel Oral Thrombin Inhibitor - Friederich, Philip W.; Keller, Tymen T.; Biemond, Bart J.; Peters, Ron J. G.; Hornberger, Wilfried; Büller, Harry R.; Levi, Marcel (Thrombosis and Haemostasis, 2000)
Current antithrombotic compounds have several limitations in clinical practice. The present study was designed to investigate a novel orally available direct thrombin inhibitor, BSF 208791. Intravenous administration of BSF 208791 showed superior antithrombotic properties as compared with Polyethylenglycol-Hirudin (PEG-Hirudin) and low molecular weight heparin (LMWH) in a model of venous thrombosis in rabbits. The thrombus growth was 22%, 30%, 37% and 50% after BSF 208791, PEG-Hirudin, LMWH, and saline administration, respectively. Moreover, bleeding time was less affected after administration of BSF 208791 as compared with PEG-Hirudin. The oral administration of BSF 208791 resulted in adequate bioavailability and significantly reduced venous thrombus growth to 36% as compared with 60% in the saline treated rabbits. The antithrombotic effect of BSF 208791 appears to be superior to PEG-Hirudin and LMWH without affecting the bleeding time. BSF 208791 is an orally available agent that might be a promising candidate for future antithrombotic therapy.
Keywords: Anticoagulants; thrombosis; coagulation; rabbits; thrombin inhibitor